Exploring online consumer ethics: Do consumer perceptions of E-ethics change according To CAD personalities? - (:unkn) unknown (My University, 2014)
Günümüzde tüketici satın alma kararlarını ve davranışlarını etkileyen en önemli faktörlerden biri Internettir ve bu nedenle tüm uygulamalar geleneksel olmayan kanallar için de adapte edilmektedir. Bu çalışma online tüketici etiği konusunda akademik araştırmalardaki büyük bir boşluğu doldurmaktadır. Bu çalışmanın amacı, online tüketici etiğini oluşturan boyutları ortaya çıkartmak ve tüketicilerin online etik algısının CAD kişilik tiplerine (Uyumlu, Agresif, Başına Buyruk) göre farklılık gösterip göstermediğini incelemektir. Veriler 725 cevaplayıcıdan yüz yüze anket yöntemiyle toplanmıştır. Online tüketici etiği boyutlarını belirleyebilmek için faktör analizi kullanılmış ve sonrasında cevaplayıcılar CAD kişilik tiplerine göre gruplara ayrılmıştır. Son olarak, hangi kişilik tipinin hangi online davranışları daha etik dışı bulduğu belirlenmiştir.

In the new era, one of the major factors influencing the buying decisions and patterns of consumers is the Internet and all concepts are being adapted to non-traditional channels. This study addresses the big gap on academic research regarding online consumer ethics. The aim of this study is to explore the dimensions that makeup online consumer ethics and to assess whether consumers online ethics perceptions show variations among the three CAD (compliant, aggressive, detached) personality types. Data were collected from 725 respondents through face-to-face surveys. Online consumer ethics dimensions were determined by factor analysis. Then, respondents were classified into groups according to CAD personality types. Finally, the personality types which perceive questionable behaviors in online behavior as more unethical are determined.
Keywords: Uluslararası İlişkiler; Siyasi Bilimler